A finite sample comparison of nonparametric estimates of the effective dose in quantal bioassay - Holger Dette; Regine Scheder (Technische Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2008)
To estimate the effective dose level ED a in the common binary response model, several parametric and nonparametric estimators have been proposed in the literature. In the present paper, we focus on nonparametric methods and present a detailed numerical comparison of four different approaches to estimate the ED a nonparametrically. The methods are briefly reviewed and their finite sample properties are studied by means of a detailed simulation study. Moreover, a data example is presented to illustrate the different concepts.
Keywords: 519; Binary response model; effective dose level; nonparametric regression; isotonic regression; order restricted inference; local linear regression